Use of Different Tissue Thromboplastins in the Control of Anticoagulant-Therapy - Verstraete, Marc; Clark, Patricia A.; Wright, Irving S. (Thrombosis and Haemostasis, 1958)
An analysis of the results of prothrombin time tests with different types of thromboplastins sheds some light on the problem why the administration of coumarin is difficult to standardize in different centers. Our present ideas on the subject, based on experimental data may be summarized as follows.Several factors of the clotting mechanism are influenced by coumarin derivatives. The action of some of these factors is by-passed in the 1-stage prothrombin time test. The decrease of the prothrombin and factor VII levels may be evaluated in the 1-stage prothrombin time determination (Quick-test). The prolongation of the prothrombin times are, however, predominantly due to the decrease of factor VII activity, the prothrombin content remaining around 50 per cent of normal during an adequate anticoagulant therapy. It is unlikely that this degree of depression of prothrombin is of major significance in interfering with the coagulation mechanism in the protection against thromboembolism. It may, however, play a minor role, which has yet to be evaluated quantitatively. An exact evaluation of factor VII is, therefore, important for the guidance of anticoagulant therapy and the method of choice is the one which is most sensitive to changes in factor VII concentration. The 1-stage prothrombin time test with a rabbit lung thromboplastin seems the most suitable method because rabbit brain preparations exhibit a factor VII-like activity that is not present in rabbit lung preparations.